Secure Recovery Procedure for Manufacturing Systems Using Synchronizing Automata and Supervisory Control Theory - Alves, Lucas V. R.; Pena, Patricia N. (IEEE transactions on automation science and engineering, 2022)
Manufacturing systems may be subject to external attacks and failures, so it is important to deal with the recovery of the system after these situations. This article deals with the problem of recovering a manufacturing system, modeled as a discrete event system (DES) using the supervisory control theory (SCT), when the control structure, called supervisor, desynchronizes from the physical plant. The desynchronization may be seen as plant and supervisor being in uncorresponding states. The recovery of the system may be attained if there is a word, the synchronizing word, that regardless the state of each one of them, brings the system and supervisor back to a known state. The concepts of synchronizing automata are used to do so. In this article, we show under what conditions a set of synchronizing plants and specifications leads to a synchronizing supervisor obtained by the SCT. The problem is extended to cope with multiple supervisors, proposing a local recovery when possible. We also present a simple way to model problems, composed of machines and buffers, as synchronizing automata such that it is always possible do restore synchronization between the control (supervisor) and the plant. Note to Practitioners -Given the unpredictability of faults and malicious attacks occurring in industrial systems, recovery strategies are crucial for a harmonic operation of the plant. The possibility of leading the system to a known state, recovering control, is of extreme importance to the safety of industrial processes. The method proposed in this article uses well-known concepts of supervisory control theory (SCT) of discrete event systems (DESs), introducing the recovery process (using recovery events) in the modeling phase such that it is possible to isolate and fix only the part of the control system subject to the fault. The result of the proposed approach allows the implementation of such control system with the recovery procedure directly in the programmable logic controllers (PLCs).